Barriers faced by people with disabilities in mainstream sports: a systematic review - Pablo Elipe-Lorenzo; Pablo Elipe-Lorenzo; Pelayo Diez-Fernández; Pelayo Diez-Fernández; Pelayo Diez-Fernández; Brais Ruibal-Lista; Brais Ruibal-Lista; Brais Ruibal-Lista; Sergio López-García; Sergio López-García; Sergio López-García; Sergio López-García (Frontiers in Sports and Active Living)
IntroductionDespite advances in inclusive policies and social awareness, the participation of people with disabilities (PwD) in mainstream sports remains limited due to numerous barriers. This systematic review seeks to identify and critically analyse the main obstacles hindering equitable participation of PwD in conventional sports, while proposing evidence-based strategies to overcome these challenges.MethodsFollowing PRISMA guidelines, a comprehensive search was conducted on Web of Science and SCOPUS databases, covering studies published between 2000 and 2024. After applying inclusion and exclusion criteria, 17 studies were selected for analysis.ResultsThe findings highlight major barriers, including insufficient training for coaches and sports club managers, negative and discriminatory attitudes, an entrenched ableist mindset, limited access to information, and a lack of accessible facilities. These factors collectively impede the active participation of PwD in sports.DiscussionTo overcome these challenges, a coordinated approach is essential, encompassing attitude transformation, targeted training for sports personnel, the implementation of inclusive policies, economic incentives, and enhanced communication strategies. Additional recommendations include integrating universal design principles into sports facilities, establishing support networks and fostering a cultural shift in societal perceptions of disability. Systematic Review RegistrationPROSPERO (CRD42024544589).